Hilbert–Huang spectral analysis of cavity flows incorporating fluidic spoilers - Bacci, David; Saddington, Alistair J. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Numerical aeroacoustic analysis was conducted on an M219 cavity geometry, incorporating signature suppression features and leading-edge fluidic spoilers. The numerical model was validated against existing experimental data. The palliative properties of fluidic spoilers were investigated at Mach numbers of 0.85, 1.20, and 1.80 with blowing coefficients of 0.03 and 0.06. The results are presented for the acoustic spectrum, and further analysis was conducted using the Hilbert–Huang methodology. The fluidic spoilers were able to considerably reduce the overall level of acoustic noise and to reduce and/or suppress the resonant modes typical of cavity flows. The effectiveness of the spoilers was a direct consequence of their effect on the detached shear layer, of which the trajectory and coherence were altered. The Hilbert–Huang spectral analysis provided an enhanced understanding of the complex nature of the aeroacoustic behavior of the cavity. Acoustic modes were identified that, together with the Rossiter–Heller tones, governed the behavior of the spectrum. This demonstrated how the generated tones, appearing inside the cavity, were a result of complex nonlinear interactions between shear-layer acoustic instabilities and centrifugal instabilities originating in the flow recirculating in the internal part of the cavity. This also demonstrated that the fundamental frequencies had frequency and amplitude modulation characteristics that spread the energy in a wide bandwidth. This is not captured by classical Fourier analysis.
Keywords: cavity; aeroacoustic; transonic; supersonic; fluidic; spoiler